Manager's Income Smoothing Actions Due to Debt Policy: The Moderating Role of Tax Avoidance - Amrie Firmansyah; Muchamad Rizal Pua Geno; Dani Kharismawan Prakosa; Pria Aji Pamungkas; Adhitya Jati Purwaka (WIM Solusi Prima, 2023)
The manager carries out income-smoothing actions to guard the stability of profit. Stability and high profits are considered an indicator of a low-risk company. The manager made this effort to increase investor belief in providing the company with source funds. This study aims to test the effect of debt policy on action income smoothing. This research also includes tax avoidance as a moderating variable in this association. This study employs data derived from financial statements of listed manufacturing companies on the Indonesian Stock Exchange from 2016 until 2021—research data sourced from www.idnfinancials.com. Samples employed in this study totaled 564 observations (firm-year). Testing hypothesis is using analysis of multiple linear regression for panel data. This study finds that debt policy is positively associated with income smoothing. However, tax avoidance has no role in moderating the association between debt policy and income smoothing. This study contributes to developing literature on income smoothing in financial accounting research frameworks using different proxies in the Indonesian context.